Review Artikel: Aktivitas Antiulcer Dari Tanaman Famili Zingiberaceae - Kinanti, Novi Sekar; Ni Kadek Warditiani (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Peptic ulcer is commonly known as gastrointestinal disease due to disturbance of normal equilibrium caused by an increase or decrease in mucosal ulceration resistance. The main risk factors for peptic ulcers are Helicobacter pylori infection and the use of non-steroidal anti-inflammatory drugs (NSAIDs). Prevention or treatment of peptic ulcers can be done by using medicinal plants that have an antiulcer effect. One of the plant families that has great potential to be used as medicine is the Zingiberaceae family, which has a gastroprotective effect. This review article was compiled with the aim of determining plants with antiulcer potential from the Zingiberaceae family. Literature study was conducted on national and international journals related to Zingiberaceae family plants that have antiulcer activity, published in the last 10 years. Referring to the results of the literature study, 8 plants of the Zingiberaceae family were successfully identified as having potential as antiulcer, including Zingiber Officinale plants with the active compound of 6-gingesulfonic acid; Zingiber cassumunar with the active compounds of alkaloids, flavonoids, saponins, tannins, quinones, and steroids; Curcuma xanthorrhiza with the active compound of curcuminoid; Curcuma longa with the active compound of curcumin; Alpinia galang with the active compound of 1’acetoxy chavicol acetate, flavonoids and saponins; Kaempferia galanga with the active compound of p-methoxy cinnamic acid; Aframomum melegueta with the active compound of 6-Paradol; and Elettaria Cardamomum with the active compound of αphellandrene.